2022
DOI: 10.3390/cancers14133048
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy for Pancreatic Cancer Detection Using Infrared Spectroscopy

Abstract: Pancreatic cancer claims over 460,000 victims per year. The carbohydrate antigen (CA) 19-9 test is the blood test used for pancreatic cancer’s detection; however, its levels can be raised in symptomatic patients with other non-malignant diseases, or with other tumors in the surrounding area. Attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy has demonstrated exceptional potential in cancer diagnostics, and its clinical implementation could represent a significant step towards early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Although there are studies investigating the use of FTIR for cancer diagnosis [ 16 , 57 , 58 , 59 , 60 , 61 , 62 ], this was not the objective of the present study. Here we pioneered combining infrared spectrum analyzes and levels of redox status markers in the blood, expanding the frontier of scientific knowledge in this area for women with HER2+ BC, HER2− BC, and BBD.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are studies investigating the use of FTIR for cancer diagnosis [ 16 , 57 , 58 , 59 , 60 , 61 , 62 ], this was not the objective of the present study. Here we pioneered combining infrared spectrum analyzes and levels of redox status markers in the blood, expanding the frontier of scientific knowledge in this area for women with HER2+ BC, HER2− BC, and BBD.…”
Section: Discussionmentioning
confidence: 99%
“…Attenuated total reflectance (ATR) spectroscopy methods and the application of high-brightness quantum cascade lasers do allow measurements in H 2 O, but deconvolution of the δ HOH and amide I bands remains challenging . Despite this, FT-IR measurements covering the full IR range (400–4000 cm –1 ) have shown promise for disease detection. Recently, a method has used thin samples of serum in transmission to detect the presence of cancers, and it was reported that the basis of the measurement was changes to the amide I region arising from variations in concentration of the 12 most abundant serum proteins . However, the limited peak resolution of IR absorption and the impact of overlapping water bands prevented the study from identifying the specific proteins or protein combinations responsible and precluded the measurement of protein concentrations.…”
Section: Amide I Spectroscopy Of Complex Proteinaceous Fluidsmentioning
confidence: 99%
“…16–18 Brennan et al 19 reported a sensitivity and specificity of 0.81 and 0.80, respectively, for the diagnosis of brain tumours in a prospectively collected clinical dataset of dried serum samples. For pancreatic cancer in particular, Sala et al 20 were able to utilise ATR-FTIR analysis of dried serum samples and machine learning to achieve an area under the receiver operating characteristic (ROC) curve (AUC) of 0.95 when classifying between pancreatic cancer and healthy samples ( n = 200), and an AUC of 0.83 when classifying between pancreatic cancer and samples from patients presenting as symptomatic of pancreatic cancer but subsequently diagnosed as non-cancerous ( n = 70). This example used machine learning methods common in the field of chemometrics, namely partial least squares (PLS) and random forest (RF).…”
Section: Introductionmentioning
confidence: 99%
“…8 One method that has developed over recent years is the use of vibrational spectroscopy as the basis of the liquid biopsy in order to capture multiple tumor and non-tumor derived bio-markers within one measurement. [11][12][13] It has the benefits of being rapid and low-cost, and can be used to analyse multiple different biofluids. 14 Vibrational spectroscopic methods such as Raman and infrared (IR) spectroscopy have previously demonstrated their potential uses within cancer detection.…”
Section: Introductionmentioning
confidence: 99%